Bone Demineralization in Postmenopausal Women: Role of Anamnestic Risk Factors. (26th July 2012) - La Vignera, Sandro; Condorelli, Rosita A.; Vicari, Enzo; Nicoletti, Chiara; Calogero, Aldo E.
Abstract : This study evaluated the effects of LT4 administration on the bone mineral density (BMD) in physiological postmenopausal women after two years of continuative treatment. 110 postmenopausal women with nodular goiter aged between 50 and 55 years were examined before and after 2 years of therapy with a fixed dose of LT4 (1.6 mcg/kg/die) for the treatment of nodular thyroid disease. The results showed that the patients on treatment with LT4 have a slight, but significant reduction of the BMD after 2 years of treatment, associated with increased serum levels of alkaline phosphatase and urinary excretion of hydroxyproline, confirming our data conducted on the same group after one year of therapy. Comparison between patients receiving LT4 (group A) or not (group B) showed that group A patients had significantly lower BMD. We demonstrated the statistically significant influence of the following risk factors on BMD: (1) body mass index < 19 kg/m 2 ; (2) the onset of menarche after the age of 15 years; (3) positive history for period of amenorrhoea; (4) nulliparity.